The differences in noradrenaline levels in Wistar and Genetic Absence Epilepsy Rats - Eryigit, T.; Oglu, M. Gulcebi Idriz; Asik, Z. N. Turgan; Kirik, D.; Onat, F. (WILEY, 2023)
35th International Epilepsy Congress, Dublin, IRELAND, SEP 02-06, 2023